ANALISIS KARATERISTIK INDIVIDU, KARATERISTIK PEKERJAAN DAN KARATERISTIK ORGANISASI TERHADAP PRESTASI KERJA - Deni Widyo Prasetyo; Sumarji Sumarji (REVITALISASI : Jurnal Ilmu Manajemen, 2020)
Human Resource Management Problems lately talked about and position becomes very important in terms of employee productivity. Because essentially HRM, an integration effort of personnel needs with organizational goals. showed that motivation is very important in the company. For this reason, among others, interesting authors to conduct research and compile the results of this study with the title: "The Influence of Individual Characteristics, Job Characteristics and Job Performance Characteristics of Organizations Against Employee In Office PPLP.PT PGRI Jombang". From the description above, the formulation of the problem posed in this study are: 1. Is there a significant relationship between motivation (which consists of individual Characteristic, Characteristic Characteristic of work and organization) together (simultaneously) on the performance of employees PPLP. PT PGRI JOMBANG? 2. Is there a significant relationship between motivation (which consists of individual Characteristic, Characteristic Characteristic of work and organization) partially on the performance of employees PPLP. PT PGRI JOMBANG? The purpose of this study is: To determine the effect of motivation variables (which consists of individual Characteristic, Characteristics of employment, organization Characteristic) jointly on the performance of employees PPLP. PT PGRI JOMBANG. To determine the effect of motivation variables (which consists of individual Characteristic, Characteristics of employment, organization Characteristic) partially on the performance of employees PPLP. PT PGRI JOMBANG. The analyzes were performed with the aim that the raw data can be meaningful in answering all questions. To qualify quantitative techniques is the analysis of the data that has been given a score according to the scale of measurement that has been applied to provide meaning. For the hypothesis used multiple linear regression analysis with the following formula: The steps to perform regression between independent variables and the dependent variable is as follows: regressed the dependent variable of work motivation (X) with independent variables Characteristics of the individual, work and Characteristic Characteristic organization (X1, X2, and X3), then F test and T-test.